Psychosocial strain and default behavior in Islamic fintech: An urban–rural analysis using general strain theory - Yudha, Ana Toni Roby Candra; Haryono, Slamet; Ardiansyah, Misnen (Universitas Negeri Surabaya, 2025)
This study examines the psychosocial determinants of loan default among Millennial and Gen Z users of Islamic fintech microfinance in Indonesia, applying General Strain Theory (GST) to compare behavioral dynamics across urban and rural contexts. Data were collected from 307 respondents and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal notable contextual differences: in urban settings, default intention is significantly influenced by social difficulties, feelings of inferiority, life dissatisfaction, loneliness, and weakened moral norms. In contrast, loneliness emerges as the only significant predictor in rural areas. Economic pressure did not serve as a major driver, emphasizing the greater influence of psychosocial strain over financial factors. These findings suggest that fintech providers should refine credit risk assessments by incorporating psychological and social indicators. Interventions such as financial literacy programs, moral reinforcement, and community-based support systems may be particularly effective, especially in rural areas where social isolation is prevalent. This study offers a novel application of GST in the Islamic fintech domain, providing theoretical advancement and practical implications for more ethical and socially inclusive fintech development.